(untitled) (Journal Resuscitatio Balcanica, 2021)
The European Resuscitation Council (ERC) has produced these Systems Saving Lives guidelines, which are based on the 2020 International Consensus on Cardiopulmonary Resuscitation Science with Treatment Recommendations. The topics covered include chain of survival, measuring performance of resuscitation, social media and smartphones apps for engaging community, European Restart a Heart Day, World Restart a Heart, KIDS SAVE LIVES campaign, early warning scores, rapid response systems, and medical emergency team, cardiac arrest centres and role of dispatcher. The Systems Saving Lives chapter describes numerous and important factors that can globally improve the management of cardiac arrest patients not as a single intervention but as a system-level approach. The aim of this paper is to provide evidence-informed best practice guidance, about interventions which can be implemented by healthcare systems to improve outcomes of out-of-hospital and/or in-hospital cardiac arrest (OHCA and IHCA). The intended audience of the paper are governments, managers of health and education systems, healthcare professionals, teachers, students and laypeople.